2017
DOI: 10.3847/1538-4365/aa7de5
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Medium-deep Survey. III. Survey of Luminous Quasars at 4.7 ≤ z ≤ 5.4*

Abstract: We present our first results of the survey for high redshift quasars at 5 z 5.7. The search for quasars in this redshift range has been known to be challenging due to limitations of filter sets used in previous studies. We conducted a quasar survey for two specific redshift ranges, 4.60 ≤ z ≤ 5.40 and 5.50 ≤ z ≤ 6.05, using multi-wavelength data that include observations using custom-designed filters, is and iz. Using these filters and a new selection technique, we were able to reduce the fraction of interlope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Recently, this LoBAL QSO was investigated by Jeon et al (2017), where their measurements of the luminosity and BH mass are consistent with those from Yi et al (2017). As the quality of near-IR spectra obtained by the Magellan telescope (see Jeon et al 2017) is much higher than that from Yi et al (2017), we use their near-IR spectra (in private communication) for J0122+1216 in this work.…”
Section: Compilation Of Optical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this LoBAL QSO was investigated by Jeon et al (2017), where their measurements of the luminosity and BH mass are consistent with those from Yi et al (2017). As the quality of near-IR spectra obtained by the Magellan telescope (see Jeon et al 2017) is much higher than that from Yi et al (2017), we use their near-IR spectra (in private communication) for J0122+1216 in this work.…”
Section: Compilation Of Optical Datamentioning
confidence: 99%
“…Notes on individual objects J0122+1216 was discovered as a quasar using the Lijiang 2.4-m Telescope (Yi et al 2015) in optical spectroscopy; later, it was further identified as a LoBAL QSO at z = 4.82 using near-IR spectroscopy (Yi et al 2017). Recently, this LoBAL QSO was investigated by Jeon et al (2017), where their measurements of the luminosity and BH mass are consistent with those from Yi et al (2017). As the quality of near-IR spectra obtained by the Magellan telescope (see Jeon et al 2017) is much higher than that from Yi et al (2017), we use their near-IR spectra (in private communication) for J0122+1216 in this work.…”
Section: Compilation Of Optical Datamentioning
confidence: 99%
“…Based on wide-field surveys, half million quasars have hitherto been discovered (e.g., Pâris et al 2017), hun- Matsuoka et al 2016;Jeon et al 2017;Yang et al 2016Yang et al , 2017Wang et al 2016;Reed et al 2017). With the identification of high redshift quasars, we are now broadening our horizon of knowledge deep into the very early universe, especially on the cosmic re-ionization epoch.…”
Section: Introductionmentioning
confidence: 99%
“…Given the spectral shape and the escape fraction of LyC photons of quasars, the contribution of quasars to the hydrogen reionizing photons can be calculated from the quasar luminosity function (LF). Therefore, many observational studies have tried to determine the LF of quasars at z > 4 (Barger et al 2003;Fan et al 2006;Jiang et al 2008;Willott et al 2010;McGreer et al 2013;Bañaods et al 2016;Yang et al 2016;Jeon et al 2017;Kim et al 2019).…”
Section: Introductionmentioning
confidence: 99%